2004
DOI: 10.1089/089771504322778668
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Group I Metabotropic Glutamate Receptors and PLC Attenuates Increases in Inositol Trisphosphate and Reduces Reactive Gliosis in Strain-Injured Astrocytes

Abstract: We have previously found that in vitro traumatic injury uncouples IP3-mediated intracellular free calcium ([Ca2+]i) signaling in astrocytes (Rzigalinski et al., 1998; Floyd et al., 2001). Since Group I metabotropic glutamate receptors (mGluRs) are coupled to IP3-mediated Ca2+ signaling, we investigated their role in the in vitro strain injury of cultured astrocytes. Astrocytes grown on Silastic membranes were labeled with 3H-myo-inositol and strain (stretch)-injured. Cells injured in the presence of LiCl to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 69 publications
(85 reference statements)
1
16
0
Order By: Relevance
“…Previous studies of 2-D stretch injury in astrocytes have demonstrated transient increases in intracellular calcium from extracellular and intracellular sources (Rzigalinski et al, 1998;Floyd et al, 2001;Neary et al, 2003). Activation of Group I metabotropic glutamate receptors, altered inositol phosphate production and uncoupling of the phospholipase C signaling pathway have been reported as acute events in astrocytic dysfunction following trauma (Floyd et al, 2001;Floyd et al, 2004). Also, increases in intracellular calcium have been linked to mitochondrial dysfunction and ATP release (Ahmed et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of 2-D stretch injury in astrocytes have demonstrated transient increases in intracellular calcium from extracellular and intracellular sources (Rzigalinski et al, 1998;Floyd et al, 2001;Neary et al, 2003). Activation of Group I metabotropic glutamate receptors, altered inositol phosphate production and uncoupling of the phospholipase C signaling pathway have been reported as acute events in astrocytic dysfunction following trauma (Floyd et al, 2001;Floyd et al, 2004). Also, increases in intracellular calcium have been linked to mitochondrial dysfunction and ATP release (Ahmed et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, necrotic cell death or disruptions in the plasma membrane may result in the release of glutamate and ATP, which have been shown to induce astrogliosis through receptor binding and subsequent initiation of signaling pathways (Franke et al, 1999;Ahmed et al, 2000;Floyd et al, 2001;Neary et al, 2003;Floyd et al, 2004;Neary et al, 2006). Therefore, the strain rate-dependent cell death may partially explain the variable astrocytotic response at the strain rates evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of group I mGluR with the antagonist AIDA in a neuronal/glial co-culture stretch-injury model resulted in reduced axonal signaling abnormalities and GFAP immunoreactivity [88]. Furthermore, N-methyl-D-aspartic acid-mediated currents were reduced in this culture model with mGluR5 agonist (RS)-2-Chloro-5-hydroxyphenylglycine (CHPG) administration, but only when glia were present [89].…”
Section: Novel Therapy: Mglur5 Agonist Chpgmentioning
confidence: 99%
“…During development of the cerebral cortex, the invasion of thalamic axons and subsequent differentiation of cortical neurons are tightly coordinated. Glutamate neurotransmission triggers a critical signalling mechanism involving the activation of PI-PLC β1 by mGluRs [94] . Activation of PI-PLC β1 via mGluR5 is critical for the coordinated development of the neocortex [45,95] .…”
Section: Metabotropic Receptors L-glutamate the Majormentioning
confidence: 99%
“…N-methyl-D-aspartate (NMDA) toxicity might be associated with NO-mediated activation of the PI-PLC δ subfamily [24,97] . Activation of group I mGluRs by (S)-3,5-dihydroxyphenylglycine, prior to NMDA exposure, reduces hippocampal susceptibility to NMDA-induced injury [93,94] . The reduced susceptibility is probably associated with PI-PLC-dependent reduction of synaptic excitation.…”
Section: Metabotropic Receptors L-glutamate the Majormentioning
confidence: 99%